The Impact of Polypharmacy on Medication Problems and Clinical Outcomes in Patients with Stage 5 Chronic Kidney Disease Undergoing Hemodialysis: A Narrative Review - Primatia Adrini Hapsari; Yulistiani Yulistiani; Githa Fungie Galistiani (Publikasi Indonesia, 2026)
Patients with stage 5 chronic kidney disease (CKD) who undergo routine hemodialysis (HD) often receive a complex treatment regimen (polypharmacy) to control comorbidities. This condition increases susceptibility to drug-related problems (DRPs) due to pharmacokinetic and pharmacodynamic changes after nephron damage. This narrative review aims to evaluate the impact of polypharmacy on the incidence of drug problems (DRPs) and its implications on various clinical outcomes, quality of life, and cost burden in stage 5 CKD patients with routine HD. This writing used a narrative review method through searching literature from various scientific data sources such as Google Scholar, PubMed, and Scince Direct, as well as national journals with a publication time span of the last 5-10 years. Literature analysis showed that polypharmacy was strongly correlated with a high incidence of moderate to major drug interaction potential (DDI) (49–89%) and drug side effect multiplication (ADRs). The use of drugs without proper dosage adjustment to the dialysis circuit triggers therapy failure. Monitoring of therapeutic outputs has been proven to integrate the dimensions of clinical data, laboratory biomarkers, economic aspects, and drug burden reduction through deregulation. Polypharmacy in ESRD-HD patients poses massive clinical and financial problems. The active involvement of clinical pharmacists through treatment reconciliation and selection of drug types with safe non-renal elimination is crucial to minimize the risk of toxicity, optimize clinical outcomes, and improve patients' quality of life.